Character Education in a Full-Day School Program: A Case Study of Third-Grade Students at SDIT Muhammadiyah Cepiring - Arif, Muhammad Yusuf Al; Wuryani, Meilan Tri; Primadoni, Ade Bagus (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
Character education is an important aspect in the formation of morals and behavior of students, especially at the elementary school level. However, social developments and environmental changes cause various challenges in the formation of student character so that effective educational strategies are needed, one of which is through the full-day school model. This study aims to analyze the implementation of character education, supporting and inhibiting factors, and the impact of the implementation of the full-day school model on the character formation of third-grade students at SDIT Muhammadiyah Cepiring. The study used a descriptive qualitative approach with research subjects including the principal, third-grade teachers, and third-grade students. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the Miles, Huberman, and Saldaña model through data condensation, data presentation, and drawing conclusions. The results of the study indicate that character education is implemented through learning, habituation, teacher role models, and Islamic school culture with a focus on religious character, responsibility, cooperation, independence, and discipline. Supporting factors include the commitment of the school community, teacher role models, and habituation programs, while obstacles come from differences in student character, lack of parental synergy, and external environmental influences. The full day school model has a positive impact on the formation of students' character.